DEVELOPMENT OF INTERACTIVE LEARNING MEDIA FOR CANVA MAGIC APPLICATION ON SHORT STORY WRITING SKILLS OF GRADE IX STUDENTS OF SMP NEGERI 2 BAROMBONG: - - Nurwahidah; Munirah; Haslinda (PT. Jurnal Center Indonesia Publisher, 2025)
This research aims to develop an interactive learning media based on the Canva Magic application to improve the short story writing skills of grade IX students of SMP Negeri 2 Barombong. The media development process follows the 4D (Define, Design, Develop, Disseminate) model, starting with an analysis of the needs of students and teachers that shows students' tendency towards visual and interactive learning media. This media is designed to present short story writing material in an interesting and easy-to-understand way. The research methods used in this study are research and development or Research and Development (R&D) with descriptive quantitative analysis methods, data collection techniques include media validation questionnaires, practical observations, and short story writing skills tests before (pretest) and after the use of media (posttest). This media prototype is designed with excellent features such as storyline templates, character illustrations, and interactive and visual step-by-step guides. The results of expert validation show a very high level of validity in the material and media aspects. The practicality test showed that the score increased from 0.73 (practical) to 0.97 (very practical). The results of the effectiveness test showed a significant increase in the short story writing skill score, with an average pretest score of 65 and the posttest increased to 90-98. So, it can be concluded that Canva Magic learning media with the AI-based Magic Write feature is effective and practical to improve short story writing skills in a creative, systematic, and meaningful way for students.